2018
DOI: 10.1177/0011000018774541
|View full text |Cite
|
Sign up to set email alerts
|

Personal Growth Initiative in the Therapeutic Process: An Exploratory Study

Abstract: Personal growth initiative (PGI), an individual's active and intentional engagement in the growth process, was originally developed as a potentially useful construct in therapy. Although it has repeatedly been related to psychological well-being and distress, few studies have examined PGI in clinical samples. The current study investigated the role of PGI in a sample of 295 clients at a community-serving training clinic. Data were collected at two time points. Confirmatory factor analyses supported a second-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 38 publications
4
33
0
7
Order By: Relevance
“…First, PGI was negatively related to distress and positively related to wellness, suggesting that higher levels of PGI may be useful in reducing distress and promoting wellness. This assertion fits with past research, which has found that clients who begin counseling with higher levels of PGI might use these skills during counseling with positive results (Weigold, Boyle, et al, 2018; see Robitschek et al, 2012). Two empirically based interventions have shown evidence for increasing PGI scores (Meyers et al, 2015; Thoen & Robitschek, 2013) and may be useful both in counseling and general outreach interventions.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…First, PGI was negatively related to distress and positively related to wellness, suggesting that higher levels of PGI may be useful in reducing distress and promoting wellness. This assertion fits with past research, which has found that clients who begin counseling with higher levels of PGI might use these skills during counseling with positive results (Weigold, Boyle, et al, 2018; see Robitschek et al, 2012). Two empirically based interventions have shown evidence for increasing PGI scores (Meyers et al, 2015; Thoen & Robitschek, 2013) and may be useful both in counseling and general outreach interventions.…”
Section: Discussionsupporting
confidence: 88%
“…PGI levels could indicate which clients are most ready to make use of the counseling process (Robitschek et al, 2012). Additionally, PGI levels have repeatedly been shown to increase during the course of counseling (Danitz et al, 2018; Robitschek et al, 2019; Weigold, Boyle, et al, 2018), suggesting that this is an optimum place for clients lower in PGI levels to learn how to actively engage in growth and, consequently, increase their wellness. However, the results of the wellness total score meta‐analysis indicate that it may be important to consider which PGI measure to use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations